Analysis of Financial Statement Preparation Based on Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) at CV Saudagar Jaya Sukses - Isnaini Isnaini; Darno Darno (Holistik Analisis Nexus, 2026)
The financial information presented in the financial statements serves to evaluate company performance, control costs, and plan future business strategies. In addition to internal parties, financial statements are also used by external parties such as creditors, investors, and government agencies. Financial statements in accordance with SAK ETAP can increase company transparency and accountability. This financial transparency and accountability will increase external parties' trust in the company. Therefore, an analysis of the preparation of financial statements at CV Saudagar Jaya Sukses is needed. This analysis aims to assess the conformity of the prepared financial statements with the provisions of SAK ETAP. This study uses a descriptive research type with a qualitative approach. The results of the study indicate that the preparation of financial statements at CV. Saudagar Jaya Sukses is still not fully in accordance with the provisions contained in SAK ETAP, so various improvements are needed to improve the quality of the resulting financial statements.